COMMUNITY MANAGEMENT INDICATORS FROM THE AXES OF COMMUNITY-BASED TOURISM. CASE: ENTREPRENEURSHIP OF THE WAORANI NATIONALITY IN YASUNÍ - Calle-Calderón, Angélica (2021)
In a development context, through a community principle, local populations generate new strategies that contribute to achieve collective goals; one of these is community tourism. Based on this thought, this study's main objective is to evaluate the community tourism enterprises of the Waorani nationality that are carried out in Yasuní, based on indicators located within each axis anchored to this management model within a framework of sustainability. For this, the analysis of the activities within this type of tourism has been considered through a mixed methodology, under a case study and ethnographic design, through field observation in the Yasuní Biosphere Reserve and interviews with key actors. As a result, different levels of compliance where obtained where the highest level is the solidarity economy and the governance axis with the lowest level. As the main conclusion, it is highlighted that the level obtained in the governance axis is strongly influenced by the organizational strengthening, which in turn, subtracts the potential in the management model controlled by the local community in the territory.